Menjadi Hamba Publikasi, Berdampakkah pada Education index di Asiatic Region? - Cliff Kohardinata; Luky Patricia Widianingsih (Journal on Education, 2023)
The purpose of this research is to obtain empirical evidence regarding the influence of publication documents, citations, and H-index on accredited international publications in the Scopus database within the Asiatic region, focusing on education in relation to the education index. The testing conducted in this study employs a multiple regression approach using data from the Asiatic region, comprising 22 countries. The data utilized in this research consists of the education index data for the year 2023, while data related to research documents, citations, and H-index are from the year 2022. The results of the study indicate that the quantity of publication documents and citations does not have an impact on the education index in the Asiatic region. Conversely, the influence of a researcher's publication productivity and impact on society (reflected by the H-index) significantly and positively affects the education index in the Asiatic region.